2011
DOI: 10.1177/1040638711407890
|View full text |Cite
|
Sign up to set email alerts
|

Quantification ofEquid herpesvirus 5DNA in clinical and necropsy specimens collected from a horse with equine multinodular pulmonary fibrosis

Abstract: A 15-year-old Belgian gelding was referred for fever, depression, and respiratory distress. Lung biopsy revealed interstitial fibrosis consistent with chronic interstitial pneumonia. Equid herpesvirus 5 (EHV-5) DNA was detected by polymerase chain reaction (PCR) in bronchoalveolar lavage and biopsy specimens. A presumptive diagnosis of equine multinodular pulmonary fibrosis (EMPF) was made, and the horse was administered a systemic treatment with corticosteroids and antiviral drugs. Despite initial clinical im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
33
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 16 publications
8
33
1
8
Order By: Relevance
“…The EHV-5 viral load in BALF of that horse was 6789 viral genome equivalents/50 ng of DNA template, while the average viral load in affected lung tissue was 12,224 viral genome equivalents/50 ng of DNA template [7]. When the EHV-5 viral load in the present EMPF study cases was converted from number of gB genes/million cells to viral genome equivalents/50 ng of DNA, the median viral load was higher than that reported by Marenzoni et al [7] with 10,516,000 gB genes/50 ng of DNA template. The single reported case as well as technical differences between the 2 studies may account for the discrepancy in the EHV-5 viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…The EHV-5 viral load in BALF of that horse was 6789 viral genome equivalents/50 ng of DNA template, while the average viral load in affected lung tissue was 12,224 viral genome equivalents/50 ng of DNA template [7]. When the EHV-5 viral load in the present EMPF study cases was converted from number of gB genes/million cells to viral genome equivalents/50 ng of DNA, the median viral load was higher than that reported by Marenzoni et al [7] with 10,516,000 gB genes/50 ng of DNA template. The single reported case as well as technical differences between the 2 studies may account for the discrepancy in the EHV-5 viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical stage of naturally occurring EMPF, EHV 5 is replicating and readily detected by PCR assays targeting structural genes (indicating lytic infection) and virus isolation[14]. Analysis of a single horse with clinical EMPF using quantitative PCR determined that the lung contained the greatest viral load, compared to other tissues, and that there was more virus present in fully developed pulmonary lesions than in less affected lung[59]. These data, as well as data from our earlier study[14], suggest that the low levels of virus present in our experimentally infected animals in the current study reflects viral kinetics present during the early stages of lung remodeling, that initiation of lung fibrosis by the virus can occur with very low amounts of latent virus, and that the virus transitions into a lytic productive infection coincident with progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…2010). Marenzoni et al . (2011) recently reported that viral load can be assessed using quantitative molecular assays and therefore EHV‐5 load in BALF used to estimate EHV‐5 load in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…described the pathology of 24 horses with an equine herpesvirus-5 (EHV-5)-associated interstitial pneumonia they named equine multinodular pulmonary fibrosis (EMPF). Since then, further cases have been reported in the USA and Europe (Hart et al 2008;Wong et al 2008;Poth et al 2009;Niedermayer et al 2010;Verryken et al 2010;Lehmbecker et al 2011;Marenzoni et al 2011;Soare et al 2011;Schwarz et al 2012). An ante mortem diagnosis was made in a few cases and subsequently even fewer horses have been treated successfully (Wong et al 2008;Niedermayer et al 2010;Verryken et al 2010;Marenzoni et al 2011).…”
Section: Introductionmentioning
confidence: 98%